The ‘power’ of international business research - Brock, Jürgen Kai-Uwe (Journal of International Business Studies, 2003)
Statistical power is the probability of accepting the null hypothesis when it is false (type II error). This research note reports the results of a statistical power analysis of international business research published in the Journal of International Business Studies, Management International Review, the Academy of Management Journal, and the Strategic Management Journal from 1990 to 1999. The results show that, although average statistical power is high compared with other disciplines, it is sufficient only for large effect sizes (ESs). Only studies published in the Journal of International Business Studies and the Academy of Management Journal achieve average statistical power levels that are sufficient for both medium and large ESs. Still the observed likelihood of committing type II errors in international business research is very high for small ESs (92%) and high for medium ESs (45%). In addition, statistical power is not explicitly mentioned or used by international business researchers, a weakness that this note is designed to change.